PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR DETEKSI DINI TUMBUH KEMBANG AUD - Meriyati Meriyati (JIV-Jurnal Ilmiah Visi, 2014)
The objective of this research is to study the effect of instructional strategy of cooperative and learning motivation on the learning outcome in the course of Early Detection of Early Aged Childrenâ€™s Development. The research conducted conducted at IAIN Raden Intan Lampung as from April through August 2013, selected 40 students randomly as samples. The research employed experimental research with treatment by level 2x2.The findings indicate (1) learning outcomes of the students with cooperative instructional strategy is higher than those who received expository instructional strategy,(2) there is interaction between instructional strategy and learning motivation of the students, (3) learning outcomes of the students with high learning motivation are higher when cooperative instructional strategy is used than when they learn with expository instructional strategy, and (4) learning outcomes of the students with low learning motivation are higher when cooperative instructional strategy is used than when they learn with expository instructional strategy. Result of the research shows that studentsâ€™ learning outcomes on early detection of development kindergarten could be improved by applying appropriate teaching instructional strategy considering their learning motivation level.